The Authority of The Supreme Court Over The Articles of Association Or By Laws of Political Parties - Widyawati Boediningsih; Norma Rahmawati (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The Articles of Association /Budget of a Political Partyor commonly referred to as the AD/ADR Political Party, are the binding rules of the entirety of a Political Party.arising,. The nature of AD/ART is almost the samewith the Rules of the invitations, everything must be subdued to AD/ART. Lately, what happened before the AD/ART of a party, who should resolve it, the Supreme Court (MA) or the Constitutional Court (MK) The two State Higher Institutions, both have the authority to review (Yudicial Review) on the rules of the invitations in the Republic of Indonesia. The Supreme Court has the authority to review the regulations of the lower legislators, while the Constitutional Court re-examines the regulations that are contrary to the 1945 Constitution.Of the two State Higher Institutions ,Who has the authority to review the ad/art of political parties in this case ? In order not to be punished and to keep the punishments , even if there is no inclusion of the rules of the invitees, because they do not include in the hierarchicalature of the regulations of the invitees, then it is expected that the Supreme Court as one of the State Higher Institutions to carry out its Assessment.